Applewhites at Wit's End - Tolan, Stephanie S. (Harper, 2012)
Great changes are in store for the highly creative and somewhat eccentric Applewhite family when money problems force them to open a summer camp for gifted children, who almost immediately begin to rebel, while a mysterious interloper watches from the woods.